World Kaleidoscope - Єременко, Олександр Михайлович; Єременко, О. М.; Ерёменко, Александр Михайлович; Yeremenko, Oleksandr M. (Philosophy and Cosmology, 2022)
The article focuses on the concept of synchronicity, which C. G. Jung developed in the late period of his creative work. Scrupulous attention is confined to the organic connection between the concept of synchronicity and the theory of archetypes. Since synchronicity is an acausal semantic coincidence of events, the article reveals the metaphysical meaning of such concepts as “coincidence”, “concordance” and “correspondence”. It is reasoned that synchronicity is a particularly strong case of coincidence; the decisive factor of synchronicity is the presence of a single meaning in events belonging to different causal chains. The connection between the concept of synchronicity and G. W. Leibniz’ concept of world harmony is shown. Three hypotheses that complement each other are put forward to explain synchronicity: 1) synchronicity as a manifestation of the eventheme nature of events; 2) synchronicity as a manifestation of the hidden plotline of the universe; 3) synchronicity and kaleidoscopicity. An eventheme is a kind of virtual cell filled with real events in history. If events that are similar in meaning and belong to different events occur with the same actors, then such events prove to be synchronic. If we use the metaphor “world is a literary text”, widespread in culture, then synchronic coincidences prove to be a kind of author’s signs scattered in this text. The image of a kaleidoscope is used to substantiate the hypothesis of world development as a change in holistic gestalts. In such a picture of the world, individual causal chains lose their relevance against the background of true causality, which is a change in holistic gestalt.

У статті зосереджено увагу на концепції синхронності, яку К. Г. Юнг розробив у пізній період своєї творчості. Пильна увага обмежується органічним зв'язком між поняттям синхронності та теорією архетипів. Оскільки синхронність — це акаузальний семантичний збіг подій, у статті розкривається метафізичний зміст таких понять, як «збіг», «узгодженість» та «відповідність». Вважається, що синхронність є особливо сильним випадком збігу; вирішальним фактором синхронності є наявність єдиного значення в подіях, що належать до різних причинно-наслідкових ланцюгів. Показано зв’язок поняття синхронності з концепцією гармонії світу Г. В. Лейбніца. Для пояснення синхронності висуваються три гіпотези, що доповнюють одна одну: 1) синхронність як прояв подієвої тематичної природи подій; 2) синхронність як прояв прихованої сюжетної лінії всесвіту; 3) синхронність і калейдоскопічність. Eventheme – це своєрідна віртуальна комірка, наповнена реальними подіями в історії. Якщо події, подібні за змістом і належать до різних подій, відбуваються з одними і тими ж суб’єктами, то такі події виявляються синхронними. Якщо використовувати поширену в культурі метафору «світ – це літературний текст», то синхронічні збіги виявляються своєрідними авторськими ознаками, розкиданими в цьому тексті. Зображення калейдоскопа використовується для обґрунтування гіпотези розвитку світу як зміни цілісних гештальтів. У такій картині світу окремі причинно-наслідкові ланцюги втрачають свою актуальність на тлі справжньої причинності, яка є зміною цілісного гештальту.
Yeremenko A. World Kaleidoscope / A. Yeremenko // Philosophy and Cosmology. - Vol. 28. - ISPC , 2022. – P. 168-184.
Keywords: C. G. Jung; G. W. Leibniz; synchronicity; coincidence; concordance; contingency; world harmony; gestalt; К. Г. Юнг; Г. В. Лейбніц; синхронність; збіг; узгодженість; випадковість; світова гармонія; гештальт; Research Subject Categories::HUMANITIES and RELIGION::History and philosophy subjects::Philosophy subjects